2019
DOI: 10.1136/bmjopen-2018-025338
|View full text |Cite
|
Sign up to set email alerts
|

Progress and setbacks in socioeconomic inequalities in adolescent health-related behaviours in Brazil: results from three cross-sectional surveys 2009–2015

Abstract: ObjectivesDespite some progress, Brazil is still one of the most unequal countries, and the extent of socioeconomic inequalities in adolescent health is unclear. We assessed trends in socioeconomic inequalities in adolescent’s health-related behaviours in Brazil between 2009 and 2015.DesignWe used cross-sectional data from the Brazilian National Survey of School Health carried out in 2009, 2012 and 2015.SettingBrazilian state capitals.ParticipantsStudents attending ninth grade from public and private schools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Intervention-focused studies are needed to assess the impact of comprehensive actions on the reduction of cluster of risk factors. Even though NCD are a problem faced mainly by adults and the elderly, it is increasingly occurring at a much younger age [55, 56], impacting lower socioeconomic groups in a disproportionate manner [36]. Thus, prevention strategies should consider the first stages of life and be directed towards the population most exposed to the main risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention-focused studies are needed to assess the impact of comprehensive actions on the reduction of cluster of risk factors. Even though NCD are a problem faced mainly by adults and the elderly, it is increasingly occurring at a much younger age [55, 56], impacting lower socioeconomic groups in a disproportionate manner [36]. Thus, prevention strategies should consider the first stages of life and be directed towards the population most exposed to the main risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…For dietary risk factors, we have used the concept of ‘regular consumption’ (≥5 times in the past week), which was validated using 24-hour recall among adolescents [34]. Low consumption of fruits and vegetables is strongly recognized by WHO as a risk factor for NCD [35], therefore, we used the complementary idea of irregular consumption (<5 times in the past week) as the risk factor [36]. On the other hand, the consumption of ultra-processed food has been recently suggested to be related to low quality diet, obesity, and NCD [3739].…”
Section: Methodsmentioning
confidence: 99%
“…The eight available response options were "I did not eat in the last 7 days," "I ate on 1 day (2, ..., 6 days) of the last 7 days," and "I ate on all of the last 7 days" [21]. For data analysis purposes, they were categorized as regularly consumed (for at least 5 days in the previous 7 days) or not [22][23][24][25][26]. All athletes are regularly enrolled in school and study in the mornings, so we consider breakfast between 6 and 8:59 am [27].…”
Section: Methodsmentioning
confidence: 99%
“… 16 17 In Brazil, previous studies have suggested that socioeconomic inequalities in access to leisure PA have decreased between 2009 and 2015, although it remains high. 18 In addition, few studies have shown the pattern of total and domain-specific PA in adolescents living in megacities in low-income to middle-income countries. 19 …”
Section: Introductionmentioning
confidence: 99%
“…16 17 In Brazil, previous studies have suggested that socioeconomic inequalities in access to leisure PA have decreased between 2009 and 2015, although it remains high. 18 In addition, few studies have shown the pattern of total and domain-specific PA in adolescents living in megacities in low-income to middleincome countries. 19 In the urban context of Sao Paulo, characterised by social fragmentation and inequalities in opportunities to engage in PA, the New Master Plan has emerged as an effective initiative to promote active life.…”
mentioning
confidence: 99%